Quantitative assessment of the repeatability of PermaGel as a ballistic tissue simulant - Read, James; Yates, Samuel; Williams, Rupert; Hazael, Rachael; Critchley, Richard (Springer, 2026)
The awareness of economic, environmental and ethical considerations centred on replication of human tissue have increased in recent years. This has driven the need to find repeatable products which can be re-used without detriment to datasets whilst providing economic benefit to research programmes and reducing the quantity of material disposed of at the end of the trials phase. This study is focussed on the ability of PermaGel to provide a repeatable medium for both survivability and lethality applications when re-used continuously. A baseline series of tests were undertaken using a single stage gas gun, with the material samples then undergoing a series of melt/recast cycles before being tested again to examine any differences in performance. The results show that a 30.40% difference in depth of penetration was observed post thermal cycling of the material, whilst a 5.36% increase in the maximum diameter of the temporary cavity was also observed. These results have raised concerns on PermaGel’s ability to be re-used accurately and recommendations on its use provided to ensure data inaccuracy risk is minimised. The findings herein have confirmed the concerns raised within the literature, provided the research community with a single point of source data, and recommended areas for future work to ensure continued characterisation is undertaken.
Keywords: 32 Biomedical and Clinical Sciences; Legal & Forensic Medicine; 3199 Other biological sciences; 3202 Clinical sciences; 3499 Other chemical sciences; Soft tissue analogue; Ballistic testing; Wound ballistics; Penetration; Repeatability